2019
DOI: 10.1097/brs.0000000000002739
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient and Inpatient Single-level Cervical Total Disc Replacement

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 23 publications
3
44
0
Order By: Relevance
“…Infection was also present in <3.7% of patients within 3 months after CDR. This result is consistent with prior studies in the literature that documented infection rates ranging from 0% to 2.9% [8,26,[28][29][30]. Lastly, reoperation or revision within 1 year after CDR occurred in <3.7% of patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Infection was also present in <3.7% of patients within 3 months after CDR. This result is consistent with prior studies in the literature that documented infection rates ranging from 0% to 2.9% [8,26,[28][29][30]. Lastly, reoperation or revision within 1 year after CDR occurred in <3.7% of patients.…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, reoperation or revision within 1 year after CDR occurred in <3.7% of patients. Other large database studies have demonstrated similarly low reoperation rates of <1%, though these studies only assessed revisions within 30 days [30].…”
Section: Discussionmentioning
confidence: 95%
“…The above factors were also individually analyzed for association with the primary outcomes using univariate logistic regression. Potential predictor variables from the univariate analyses that were either significant ( P < .05) or trended toward significance ( P < .10), 14 as well as surgical setting, were then evaluated for significance ( P < .05) as independent predictors and control variables in a series of multivariate logistic regression analyses of the primary outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Low complication rates for outpatient discectomy have been well described. [27][28][29][30] Moreover, Segal et al 14 demonstrated no significant difference in rates of readmission, reoperation, or complication when comparing inpatient to outpatient cervical disc replacement.…”
Section: Comparison Of Setting: Primary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation